2015
DOI: 10.1063/1.4926808
|View full text |Cite
|
Sign up to set email alerts
|

Correlated high-resolution x-ray diffraction, photoluminescence, and atom probe tomography analysis of continuous and discontinuous InxGa1−xN quantum wells

Abstract: Articles you may be interested inSurface plasmon enhanced spontaneous emission rate of InGaN ∕ GaN quantum wells probed by time-resolved photoluminescence spectroscopy Appl. Phys. Lett.Effects of growth interruption on the optical and the structural properties of InGaN/GaN quantum wells grown by metalorganic chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Other than increasing the QW growth temperature, a temperature ramp between the growth of QW and quantum barrier could provide a similar thermal budget for the removal of some QW material to form GWWFs [10]. Introducing H 2 to the carrier gas during growth of the GaN barrier has also been shown to cause discontinuous QWs that are narrower and of lower indium content [26]. Additionally, as GWWFs are mostly aligned with the surface terrace edges [15], which are related to the substrate miscut, the formation of GWWFs can be affected by substrate miscut angles.…”
Section: Resultsmentioning
confidence: 99%
“…Other than increasing the QW growth temperature, a temperature ramp between the growth of QW and quantum barrier could provide a similar thermal budget for the removal of some QW material to form GWWFs [10]. Introducing H 2 to the carrier gas during growth of the GaN barrier has also been shown to cause discontinuous QWs that are narrower and of lower indium content [26]. Additionally, as GWWFs are mostly aligned with the surface terrace edges [15], which are related to the substrate miscut, the formation of GWWFs can be affected by substrate miscut angles.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the quality and the uniform distribution of indium of MQWs, many researchers have reported the effect of the presence of H2 during the MQWs growth. Some researchers find that the presence of H2 during the MQWs growth will create smoother surface and enhanced photoluminescence (PL) [8], [9]. Ren et al reported that adopting the H2 pre-flow prior to the InGaN quantum well growth will make the interface smoother and enhance the PL intensity [10].…”
Section: Introductionmentioning
confidence: 99%
“…8) However, our results and those of other groups show that the nominal IQE is dramatically improved when hydrogen is used either for GaN growth or interruption. 11,17) On the basis of the results of the previous TDPL characteristics analysis, it is reasonable to deduce that the high luminous efficiency of the hydrogen-treated sample originates from the alleviation of indium segregation and the reduction in defect density at the QW=QB upper interface, rather than gross thickness fluctuations.…”
mentioning
confidence: 99%
“…Second, the initially grown GaN LT-cap layer only partially covers the InGaN well surface, and the indium atoms on the uncovered InGaN well surface may be removed or etched out by hydrogen during GaN LT-cap layer growth. 17) In addition, the upper interface has a higher indium content than does the bottom interface, 11) which may aggravate the decrease in the average indium content in InGaN wells. As a result, the presence of H 2 in GaN LT-cap layer growth may induce severe well thickness variation, as well as the reductions in the indium content and thickness of the InGaN well layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation